Who will direct your actors? The truth about radio direction - Sims, Martin (Henry Stewart Talks, 2008)
Why you need a radio commercial director, How a director can bring a script to life, The importance of pre-production meetings, Understanding the studio dynamic, The problems with directing actors, How to make better use of your radio budgets
Archived at 2022/03/17